ANALISIS PENGARUH DESENTRALISASI FISKAL TERHADAP AKSESABILITAS PENDIDIKAN DI INDONESIA PERIODE SEBELUM DAN SETELAH DESENTRALISASI FISKAL - Dayu Larasati; Hendra Saputra (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2014)
Fiscal decentralization carried out with the belief that local government understand the needs of people in the region better than the central government does. With a policy of fiscal decentralization, local government are expected to achieve a more equitable social welfare. This research was conducted because of the increasing demands of society that the government should pay attention to their needs, especially education that is now a major requirement for the community and even falls into one of national priorities . The conclusions of this study are : 1 increased own source revenue (PAD), general purpose grant (DAU) and special purpose grant (DAK) of education can increase educational spending by district/municipality local government ; 2. Increase spending on education by district/municipality local government can improve the accessibility of education by the public 3. The welfare of district/municipality can increase educational spending by district/municipality local government and accessibility of public education ; 4. In rich district/municipality, the increase in local government education spending has greater effect on increasing accesibility of public education than in poor district/municipality; 5. Fiscal decentralization policy can improve the accessibility of education by the community.